Strategy of introduction of information system in trade and logistics company - Zhilkina, Yana; Kukartsev, Vladislav; Nizameeva, Alena; Pinchuk, Ivan; Ageev, Daniel (E3S web of conferences, 2023)
In the modern world, technologies and market requirements are constantly changing, and the introduction of modern information systems is necessary for the successful functioning of companies in the field of trade and logistics. These systems automate processes, simplify management and increase efficiency. The advantages of implementing information systems are discussed in this article, as well as the problems that companies may face in this process. The inconsistency of the company’s hardware architecture and network with the requirements, as well as the lack of resources, including qualified personnel and finances, are the main problems. Incorrect choice of information system or resistance from employees can also cause problems. Taking into account all these factors and overcoming them is important for the successful implementation of information systems in the field of trade and logistics in order to get all the benefits from the new system.